Comparison of Broth Microdilution and Colistin Disk Elution Methods for the Determination of Colistin Susceptibility in Multidrug Resistant Pseudomonas aeruginosa Isolates - Neslihan ARICI; Nilgün KANSAK; Rıza ADALETİ; Sebahat AKSARAY (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2023)
Introduction: Colistin is increasingly used as a last-choice antimicrobial in the treatment of infections caused by multidrug-resistant Pseudomonas aeruginosa isolates. Due to the recent increase in colistin resistance around the world, the need for reliable methods for susceptibility testing has become more important. In this study, it was aimed to determine the performance of the broth disc elution (BDE) test, which was developed as an alternative to the reference broth microdilution (BMD) method. Materials and Methods: Fourty eight multidrug resistant Pseudomonas aeruginosa strains isolated from various clinical specimens were included in the study. The BMD method was performed according to the recommendations of the ISO-standard (20776-1), and the BDE test was done according to the Clinical and Laboratory Standards Institute (CLSI) recommendations. The categorical agreement, major error, and very major error (VME) rates of the BDE test were determined by comparing with the BMD method. Results: By using the reference BMD method, 47 of 48 isolates were found to be susceptible (98%), and one was found to be resistant (2%). According to BMD test, the minimum inhibitory concentration distribution of the isolates was between 0.25-64 mg/l. The BDE test also correctly detected 47 susceptible and 1 resistant isolates. When the BDE test was compared with the BMD, the rate of categorical agreement was found to be 100%. No major or VMEs were detected. Conclusion: The BDE test performed very well in determining colistin susceptibility in multidrug resistant P. aeruginosa isolates. Therefore, we think that the BDE test can be used as a practical and reliable method in laboratories with limited resources where it is not possible to perform the reference BMD method.